(untitled) (Swiss Medical Weekly, 2022)
BACKGROUND: In Switzerland, 519 patients received an organ in 2020. In total, 2124 patients were on the donor organ waiting list in 2020. There are many more people who need an organ than people willing to donate one. Therefore, 43 organs had to be imported from outside of Switzerland and this number was still not sufficient. This disproportion of patients needing an organ and available donor organs is the subject of ongoing discussion. A solution to this problem might be provided by a popular initiative proposing that every single resident of Switzerland should be an organ donor, unless a person explicitly rejects organ donation. We surveyed the patients in a single tertiary care emergency department (ED) to determine whether they had an organ donor card or were registered in the Swiss National Organ Donor Registry (NODR), the frequency of willingness to donate organs and which factors were associated with being an organ donor. METHODS: In a prospective anonymised survey during July 2019, we enrolled patients who visited a Swiss tertiary care ED, during one week from 8:00 to 18:00, two weeks from 14:00 to 23:00 and one week from 23:00 to 8:00. The patients completed a written, standardised and self-administrated questionnaire during the waiting time in the ED. Descriptive, uni- and multivariable logistic regression analysis were performed. RESULTS: We enrolled 307 ED patients, of whom 62 (20.2%) were donor card holders or were registered in the Swiss NODR. Of these, 53 (85.5%) would be willing to donate organs. The remaining nine (14.5%) were not willed to donate an organ; the reasons for this were very heterogeneous. In contrast, the two leading reasons for willingness to donate organs were: to help after death (94.3%) and to free relatives from the task of making the decision (43.4%). From the 245 (79.8%) participants who did not have an organ donor card or were not registered, 84 respondents (34.3%) lacked knowledge of this topic, 65 (26.5%) had not yet thought about the topic and 51 (20.8%) had not yet had time to take care of this issue. Blood donation (odds ratio [OR] 2.1, 95% confidence interval [CI] 1.1–3.9; p = 0.018) or receiving a transplant in the past (OR 6.1, 95% CI 1.3–29.1; p = 0.023) and having a university degree (OR 1.8, 95% CI 1.0–3.2; p = 0.049) were factors associated with being an organ donor card holder. CONCLUSIONS: Only one in five ED patients had a fully completed organ donor card or were registered in the Swiss NODR. Of these, the great majority were willing to donate organs. Most of the ED patients who did not have an organ donor card or were not registered in the NODR lacked knowledge and information about the topic, had not yet thought about it or had not had time to deal with this issue. Factors such as a positive history of blood donation, organ transplantation in the past or having a university degree were associated with having an organ donor card. In order to increase the willingness to donate organs in the future, it is of immense importance to provide better information and more details and knowledge about this important topic.